Influence of γ-Irradiation on Initial Magnetic Permeability of Amorphous and Nanocrystalline Fe−Si−B-Based Alloys - Povarchuk, V.Yu.; Nosenko, V.K.; Kraitchinskii, A.M.; Neimash, V.B.; Kras’ko, M.M.; Maslov, V.V. (Ukrainian Journal of Physics, 2012)
By determining the inductance factor, the dependence of the initial magnetic permeability μi of amorphous and nanocrystalline Fe–Si–B-based alloys on the γ-irradiation dose has been studied. The doping of amorphous Fe–Si–B alloys with nickel and molybdenum is found to enhance the radiation sensitivity of μi. The initial magnetic permeability of nanocrystalline magnetic alloys is determined to be less sensitive to the action of γ-radiation than that of doped amorphous ones. A hypothesis is put forward that the influence of radiation on the initial magnetic permeability is associated with the creation of non-magnetic inclusions in the structure of amorphous alloys and in the amorphous matrix of nanocrystalline alloys.